A Critical Entry to the Concept of Farrah-e Izadi: Essence or Acquisition by Relying on the Concept of Šāhī Ārmānī - Ahmad Azizkhani; Saeid Ghazanfarri (Comparative Theology)
Revisiting the fundamental concepts of Šāhī Ārmānī in ancient Iran is essential. The oral traditions of ancient Iranian civilization, the richness of Iranian mythology, and the literary transmission of ancient teachings—often laden with metaphor—have all contributed to the challenges in achieving a clear and accurate understanding of these core concepts. One such concept, Farrah-e Izadi (Divine Glory), remains particularly ambiguous due to these factors. Furthermore, grasping the political, cultural, and social dynamics of ancient Iran is intricately linked to this idea. Farrah symbolizes the sacred legitimacy of Šāhī Ārmānī. However, this association has led to various misinterpretations, obscuring the original meaning of Šāhī Ārmānī in ancient Iranian thought. The intangible nature of Farrah has caused many to perceive it solely as a divine gift, often overlooking its earthly and acquired dimensions. This study, employing a descriptive-analytical approach and utilizing primary sources, explored the earthly and acquired aspects of the concept of Farrah. Through an analytical narrative, it sought to reinterpret this concept within the framework of Šāhī Ārmānī, emphasizing its acquired dimensions and aiming to strengthen the nuanced understanding of subjectivity in ancient Iran from this perspective.